A Arquiconfraria do Cordão de São Francisco da Vila Nova da Rainha do Caeté: aspecto histórico, devocional e artístico: The Archconfraternity of Saint Francis Cord of Vila Nova da Rainha do Caeté: historical, devotional and artistic aspect (Revista de História da UEG (REVHIST), 2019)
Abstract: The purpose of this study was to analyze the establishment and development of the Archconfraternity of Saint Francis Cord of Vila Nova da Rainha do Caeté from the handwritten documentation produced by the religious association of “non-white” laymen, imposed in this location in the year of 1782. By combining such sources with testamentary, governmental and iconographic records – the latter present at the temple, currently named Igreja de São Francisco de Assis de Caeté-MG –, we establish to understand the associative momentum of the managing Board from the year of approval of its internal regulation, such as the devotional and art scene of the corporation.Keywords: Archconfraternity of Saint Francis Cord. Free-colored men. Cult. Centuries XVIII-XIX. Minas Gerais.